(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Background: Respiratory Distress Syndrome is a major cause of morbidity and mortality in premature neonates. MPV is an indicator of platelet function. It may be considered a risk factor for developing RDS. Objective: to evaluate the role of Mean Platelet Volume as a prognostic indicator in the occurrence of respiratory distress syndrome in premature infants. Materials and Methods: An analytical study)case-control) conducted on103 premature:49 males and 54 females, and who were admitted to the Neonatal Intensive Care Department at Tishreen University Hospital between July 2022 and July 2023 after applying exclusion criteria, study sample was divided into two groups: 56.3% of premature infants with RDS and 43.7% premature infants without RDS. Blood samples were taken on the first and third day of life to conduct complete blood count including (number of platelets and their average size). Results: the mean of MPV on the first day of life was higher in the RDS group than in the other group with a statistically significant difference. MPV on the third day of life was higher in the RDS group±10.89)1.3(versus±9.21) 1.3) with P:0.0001. It was the best cut-off value for MPV on day1 that could be used for prediction RDS is9.9 fl with sensitivity 77.8% and specificity 62.1% respectively. elevation of the mean values of MPV on the first and third days of life increased with increasing severity of RDS. In addition, the mean values of MPV on the first day were higher in the group of premature infants who died(11.84±1.1 versus9.85±1.4, P:0.0001) Conclusion: : MPV is a simple, readily available biomarker that can be used as an aid to predict RDS incidence.